A critical review of the global legal framework on piracy: 40 years after UNCLOS. (2nd January 2022) - Wambua, Musili
ABSTRACT : The Third United Nations Conference on the Law of the Sea (UNCLOS III) marked the last stage in developing a comprehensive and codified legal regime for ocean governance. The resultant United Nations Convention on the Law of the Sea (UNCLOS) was a compromise instrument that accommodated the interests of diverse groups at UNCLOS III. As a compromise instrument, the Convention did not address all pertinent issues on ocean governance. Some of the fundamental shortcomings of UNCLOS include a restricted definition of piracy under Article 101 and lack of a definitive enforcement mechanism under Article 105. The article highlights these shortfalls and outlines the efforts by the global community to address the shortcomings in order to combat maritime security threats, both at regional and global levels.